PROBLEM-BASED COMPREHENSIVE UNDERSTANDING OF THE SITUATION FOR ACHIEVING FINANCIAL INDEPENDENCE FOR WOMEN - Dr. Aman Sharma (International Scientific and Current Research Conferences, 2023)
This paper underlines on the utilization of metacognition in obtaining for enchancment of progressive competencies amongst ladies. The creator has fostered an Issue put collectively Learning Situation pivoted with appreciate to metacognition of studying and dispatched them as Mixed Learning Mediation in Huzurpaga School of Ladies in Pune City for fifty two days. It was once found that it has really helpful effect on obtaining of Pioneering Abilities amongst ladies. There had been three modules of the Mixed Learning Mediation. Present area portrays Market assessing out of the three modules proposed in the Intercession.